Pengaruh Metode Pencucian Dengan Air Garam Terendam Terhadap Kontaminasi Telur Cacing Parasit Usus Pada Sayur Lalapan Kubis (Brassica Oleracea Var. Capitata) - Benaya Yamin Onesiforus; Elisa Rinihapsari; Puri Dwi Asih (Sekolah Tinggi Ilmu Kesehatan Kesetiakawanan Sosial Indonesia, 2022)
Cabbage (Brassica oleracea var. capitata) is commonly consumed in raw as lalapan (secondary dish) in daily meal. Lalapan is raw vegetables which is commonly consumed in Javanese people as secondary dish. Consumption of raw vegetables has a potential for helminth infection. This research is an experimental study. In this study, three methods of washing cabbage by using running water, submerged water, and submerged brine were carried out. Different treatments aim to find out more effective methods in preventing the transmtion of parasitic helminths through cabbage vegetables. In the washing method using running water, it is hoped that worm eggs will be washed away along with the dirt in the cabbage vegetable strands. In the washing method using submerged water, it is hoped that worm eggs can be detached from the strands of cabbage vegetables and float on the surface of the water used for washing. Meanwhile, in the washing method using submerged brine, it is expected that the worm eggs will fall and settle at the bottom of the washing container. Chi-square test result in p value = 0,273 between washing method using submerged water and submerged brine, which can be interpreted as there is no difference in contamination results between the washing method using submerged water and submerged brine. Running water gave the best result with no contamination found in cabbage leaves.